Nanotechnology-based drug delivery systems: past, present and future - Riana Awang Saman; Mohammad Iqbal (Springer, Cham, 2018)
The methods involved in delivering drugs to target sites will have significant impact on the effectiveness of the drugs release. Absorption of high concentration of drugs have some toxicity effect meanwhile having low concentration may prove how low the therapeutic benefit the drugs hold, putting aside other various drawbacks. This chapter outlines how nanotechnology has developed some advance drug delivery system and how the development moves along throughout the years for a better future of medical treatments.